Toxic Effects of Cd and Zn on the Photosynthetic Apparatus of the Arabidopsis halleri and Arabidopsis arenosa Pseudo-Metallophytes - Szopiński, Michał; Sitko, Krzysztof; Gieroń, Żaneta; Rusinowski, Szymon; Corso, Massimiliano; Hermans, Christian; Verbruggen, Nathalie; Małkowski, Eugeniusz (Frontiers in Plant Science, 2019)
Trace Metal Elements (TME) hyperaccumulation and hypertolerance are highly variable traits in pseudo-metallophytes. In this study we compared the impact of high Cd or Zn doses on the photosynthetic apparatus of two Arabidopsis arenosa and Arabidopsis halleri pseudo-metallophytes growing on the same contaminated site in the south of Poland. Plants were grown in hydroponic culture with a modified Hoagland medium for six weeks, and then treated with 1.0 mM Cd or 5.0 mM Zn for 5 d. Chlorophyll a fluorescence and pigment content were measured after 0, 24, 48, 84 and 120 h in plants grown in control and subjected to metal treatment. In both species exposure to TME excess caused a decrease in chlorophyll and an increase in anthocyanin content in leaves with respect to what was observed in the control condition. After 5 d Cd treatment, energy absorbance, electron transport flux and the percentage of active reaction centers decreased more in A. arenosa than in A. halleri. However, the electron transport flux in the leaves of A. arenosa was less affected than in A. halleri. Zn treatment had significantly less toxic effect than Cd excess on A. halleri and it caused only a decrease in the electron transport flux. On the other hand A. arenosa plants treated with Zn excess reacted as strongly as in the Cd treatment and a significant decrease in all photosynthetic parameters describing energy fluxes was found. The two species showed contrasting behavior in TME accumulation. A. arenosa accumulated almost threefold higher Cd concentration in the shoot than A. halleri. On the opposite, three-fold increase in Zn concentration was measured in A. halleri leaves with respect to what was observed in A. arenosa. Our results showed that both plant species are resistant to high Cd or Zn doses, however, the photosynthetic apparatus of two metallicolous Arabidopsis species responded differently to the toxic effect of Cd and Zn.